Development of Dribbling Learning Model in Football Games Through Playing Approach for Students of SMP PGRI 2 Cilongok Banyumas Regency in the 2023 Academic Year - Didi Muhtarom; Dian Anggi Permadi; Boby Agustan; Oman Hadiana; Ramdhani Rahman (International Journal of Studies in International Education, 2024)
Learning football is one of the lessons that seventh grade junior high school students must learn. However, the reality in the field is that there are still many obstacles faced by both teachers and students. One of them is the development of dribbling in playing violin and the lack of game practice in carrying out soccer lessons. In other words, students are only given theory and are not helped with playing practice. For this reason, the problem formulation can be drawn: How is the development of soccer dribbling learning after learning using a playing approach for class VII students at SMP PGRI 2 Cilongok? The aim of this research is to determine the development of dribbling learning in the game of soccer through a playing approach for class VII students at SMP PGRI 2 Cilongok. This research method is to use an experimental method with pretest and posttest. The total population was 25 people with data collection techniques through pre-test and post-test. Data analysis will be carried out using the morality test, homogeneity test and t test. The results of research on playing approaches can have a significant influence on improving dribbling abilities in students at PGRI 2 Cilongok Middle School, Banyumas Regency.